Trends in the Development of the International Trade Law - DIACONESCU, Amelia (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
The international trade exchanges and their continuous development imply the existence of certain regulations under the shape of laws, conventions, treaties, legal tools which ensure stability and legal security for the traders and the commercial relationships. The process to issue cohesive regulations in the matter of the international trade takes place not only in the area of direct relationships between states, but most often under the auspices of international organizations.